Challenges of a new academic discourse: an investigation into the reading and writing practices of first-year chemical engineering students at a South African University - Vicatos, Evelyn Magdalene (School of Education, 2021)
The challenges for a diverse intake of first-year engineering students, when acquiring a new academic discourse during the transition to university, has triggered this study of literacy practices in the first project task in a core first-year chemical engineering course, in a four-year undergraduate degree programme at a South African university. Most reviewed engineering courses incorporate a socialisation approach into valued practices including literacy skills, particularly writing. Research on such courses focuses on the outcome of successful acquisition of a new discourse, rather than the process. This study focuses not only on the successful outcome, but also on describing and explaining the process of acquisition in the classroom leading to this outcome. It specifically investigates what is valued in the reading and writing tasks of the first project and the qualitative detail of students' writing, as they utilise school resources to fulfil their interpretations of the literacy task requirements. The study followed an ethnographic case study approach, informed by Norman Fairclough's language and social theory and his related methodology of critical discourse analysis. It included observation, interviews with twelve selected students, the course convenor and lecturer, and the analysis of course documents and written texts of two students, each from a selected group. The analysis shows that there is a strong socialisation approach into valued literacy and other practices in the course project work from the start of the programme. This requires integrating valued knowledge, literacies and ways of being and interacting into different learning areas (called “strands”), related to professional graduate outcomes, and with activities which should be completed in the valued prescribed way to meet these outcomes. The analysis also shows that the project work includes potentially transformative aspects, associated with an Academic Literacies perspective, by including current shifts in valued knowledge and by extending support for a gradual socialisation process with projects throughout the degree programme. The key finding of this study is that the socialisation process is very complex, not only because of the type of literacy resources which students bring from school, but because of multiple issues occurring in the classroom when they interpret and produce texts. These include the range of information given meaning in the course documents, time pressure related to competing demands of various strands, and power relations within groupwork. The results can inform further collaborative educational development and longitudinal research between disciplinary and literacy staff to strengthen the existing support for this complex process. This would increase the transformative potential of the course project work by helping students to access valued practices for their first task within a new academic discourse, especially for a diverse student cohort.